Existence of infinitely many nodal solutions for a superlinear Neumann boundary value problem. (13th November 2005) - Qian, Aixia
Abstract : We study the existence of a class of nonlinear elliptic equation with Neumann boundary condition, and obtain infinitely many nodal solutions. The study of such a problem is based on the variational methods and critical point theory. We prove the conclusion by using the symmetric mountain-pass theorem under the Cerami condition.